The Effect of Counselling Intervention during Antenatal Care on the Knowledge and Attitude about Danger Signs in Pregnancy: A Cross-Sectional Study in Takalar Regency - Nurhikmah; Tahir Abdullah; Stang; Suriah; Andi Imam Arundhana; Syamsuar Manyullei (Journal of Pharmacy and Nutrition Sciences, 2020)
Objective: This study was to examine the effects of counselling delivered during antenatal care on the knowledge and attitudes of pregnant women about danger signs in pregnancy. Methods: This was a pre-experimental design using one group pre- and post-test only. This study was conducted in Takalar, specifically within Sanrobone Community Health Service working area. Takalar is located in South Sulawesi Province Indonesia and this area is coastal with the majority of people working as a fisherman. Participants of this study were pregnant women living in the villages which are included in the working area of Sanrobone Community Health Service. Results: The study shows that counselling improved knowledge and attitude of pregnant women about danger signs in pregnancy (p=0.011 and p=0.025, respectively). The number of pregnant women with good knowledge and positive attitude increased after the intervention (43.8% vs 93.8%, 62.5% vs 93.8%, respectively). Conclusions: In can be concluded that intervention by means of counselling can improve the knowledge and attitude of pregnant women about danger signs in pregnancy. Therefore, it is important to implement the counselling program delivered by health workers in Community Health Service in order to mitigate the risk of maternal mortality.